(untitled) (Journal of the College of Education for Women, 2021)
This study aims to examine the technologies of education and their importance, shedding light on their reality and status in Sudan especially in the secondary stage. It has become necessary to invest these technologies and include them in different aspects of the technical education curricula. Such a step helps cope with the innovative scientific development in the advanced countries, qualify professors and technicians, develop the factories and workshops, and create an attractive technical educational environment to the pupils. Thus, the researcher has adopted a descriptive analytical approach that is based on conducting pilot visits to certain technical schools in Al-Khartoum state. Different aspects of such schools were examined, such as: (crafts, commercial, female technical). Moreover, some interviews were made with a purposeful sample of headmasters and teachers of schools, taking into account their notes and suggestions. In addition, the technical education department at the ministry of education was visited to stand upon the workshops’ recommendations and the scholarly papers presented in the field of technical education in Sudan. The study finally has concluded that the technical education in Sudan needs much more focus on using modern technology to cope with the scientific development of curriculla, educators and different educational tools. In addition, many parents do not encourage their children to go for such a type of education as they ignore the value of technical education.